Dual In Situ Generation of Aliphatic Vinyl Ethers and Electron-Deficient ortho-Quinone Methides for Inverse-Electron-Demand [4+2] Cycloaddition: A Selective One-Pot Synthesis of 3-Alkylchromanes - Tanaka, Kenta; Ueno, Ko; Tanaka, Yuta; Ohtsuka, Naoya; Asada, Yosuke; Kishimoto, Mami; Sunaga, Shuto; Hoshino, Yujiro; Honda, Kiyoshi (Synlett, 2020)
An inverse-electron-demand [4+2] cycloaddition of in situ generated aliphatic vinyl ethers and electron-deficient ortho-quinone methides (o-QMs) has been developed. The reaction of in situ generated aliphatic vinyl ethers with o-QMs afforded the corresponding 3-alkylchromanes with high stereo- and regioselectivities. The method provides a versatile access to functionalized 3-alkylchromanes and it constitutes a useful tool for the synthesis of biologically active chromanes.
Keywords: catalysis; [4+2] cycloaddition; vinyl ethers; ortho-quinone methides; salicylaldehydes; chromanes